Evolution of Low‐Frequency Vibrational Modes in Ultrathin GeSbTe Films. Issue 3 (16th March 2021) - Zallo, Eugenio; Dragoni, Daniele; Zaytseva, Yuliya; Cecchi, Stefano; Borgardt, Nikolai I.; Bernasconi, Marco; Calarco, Raffaella
Abstract : In article number 2000434, Eugenio Zallo and co‐workers report a methodology based on the Raman technique for the measurement of the layer number in ultrathin GeSbTe films obtained by molecular beam epitaxy. The experimental and theoretical evolution of the in‐plane low‐frequency vibrational modes of Ge2 Sb2 Te5 from bulk down to a single lamella is demonstrated. The energy shift is mainly related to the weak van der Waals interactions between the layers.